Essential Oils Against Foodborne Pathogens and Spoilage Bacteria in Minced Meat - Barbosa, Lidiane Nunes; Mores Rall, Vera Lucia; Henrique Fernandes, Ana Angelica [UNESP]; Ushimaru, Priscila Ikeda; Probst, Isabella da Silva; Fernandes, Ary [UNESP] (Mary Ann Liebert, Inc., 2009)
The antimicrobial activity of essential oils of oregano, thyme, basil, marjoram, lemongrass, ginger, and clove was investigated in vitro by agar dilution method and minimal inhibitory concentration (MIC) determination against Gram-positive (Staphylococcus aureus and Listeria monocytogenes) and Gram-negative strains (Escherichia coli and Salmonella Enteritidis). MIC(90%) values were tested against bacterial strains inoculated experimentally in irradiated minced meat and against natural microbiota (aerobic or facultative, mesophilic, and psychrotrophic bacteria) found in minced meat samples. MIC(90%) values ranged from 0.05% v/v (lemongrass oil) to 0.46% v/v (marjoram oil) to Gram-positive bacteria and from 0.10% v/v (clove oil) to 0.56% v/v (ginger oil) to Gram-negative strains. However, the MIC(90%) assessed on minced meat inoculated experimentally with foodborne pathogen strains and against natural microbiota of meat did not show the same effectiveness, and 1.3 and 1.0 were the highest log CFU/g reduction values obtained against tested microorganisms.